SYSTEMATICS REVIEW OF VLOGS INTEGRATION IN ELT - Ratu Ikrima Muzqia; Sifa Herawati; Nafan Tarihoran (Adisam Publisher, 2025)
The integration of vlogs in English Language Teaching (ELT) has gained significant attention due to their potential to increase student's motivation, engagement, and speaking proficiency. This systematic review synthesizes research findings on vlog-based learning and its impact on ELT. The research highlights the benefits of vlogging in fostering self-confidence, improving pronunciation, and creating an interactive learning environment. Despite these benefits, challenges such as technical limitations, speaking anxiety, and time constraints hinder effective implementation. Addressing these challenges through pedagogical strategies and institutional support is crucial to optimizing vlog-based learning. Future research should focus on innovative approaches to overcome these barriers and examine the long-term effects of vlogging on language learning outcomes.